2016
DOI: 10.3892/mmr.2016.5129
|View full text |Cite
|
Sign up to set email alerts
|

The herbal extract KCHO-1 exerts a neuroprotective effect by ameliorating oxidative stress via heme oxygenase-1 upregulation

Abstract: KCHO-1 is a novel product comprised of 30% ethanol extracts obtained from nine medical herbs, which are commonly used in traditional Korean and Chinese medicine. The nine herbs include Curcuma longa, Salvia miltiorrhiza, Gastrodia elata, Chaenomeles sinensis, Polygala tenuifolia, Paeonia japonica, Glycyrrhiza uralensis, Atractylodes japonica and processed Aconitum carmichaeli. Recent studies have reported the beneficial effects of these herbs. The present study aimed to investigate the direct neuroprotective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key transcription factor which controls the redox state as the cell’s main defense mechanism against oxidative stress. 6 , 7 Nrf2 acts by activating the antioxidant response, which induces the transcription of a wide range of genes that are able to counteract the harmful effects of oxidative stress, thus restoring intracellular homeostasis. 8 Under basal conditions, Nrf2 is localized in the cytoplasm, anchored by the Kelch-like ECH-associated protein (Keap1), and degraded by the ubiquitin-26S proteasome pathway, with a half-life of 20 min.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key transcription factor which controls the redox state as the cell’s main defense mechanism against oxidative stress. 6 , 7 Nrf2 acts by activating the antioxidant response, which induces the transcription of a wide range of genes that are able to counteract the harmful effects of oxidative stress, thus restoring intracellular homeostasis. 8 Under basal conditions, Nrf2 is localized in the cytoplasm, anchored by the Kelch-like ECH-associated protein (Keap1), and degraded by the ubiquitin-26S proteasome pathway, with a half-life of 20 min.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that Mecasin, a herbal extract, has neuro-protective and anti-neuroinflammatory effects, and its safety has been proven in both in vitro and in vivo trials [ 8 14 ]; it has been shown to reduce the progression of ALS in Korean Medicine Clinics [ 6 , 7 ]. No previous randomized controlled trial has examined the effects of Mecasin for the treatment of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that 30 days of the combined therapy led to a K-ALSFRS-R score increase from 28.42 ± 7.83 to 29.08 ± 7.99 [ 7 ]. Mecasin, also known as KCHO-1, a herbal extract from modified jakyakgamchobuja-tang , has shown neuro-protective and anti-neuroinflammatory effects and safety in both in vitro and in vivo trials [ 8 14 ]. The aim of this study was to develop a protocol to assess the optimal dosage of Mecasin, and to test whether Mecasin alleviates the functional decline in patients with ALS.…”
Section: Introductionmentioning
confidence: 99%
“…KCHO‐1 has been shown to reduce oxidative damage caused by glutamate and H 2 O 2 in nerve cells such as HT22 mouse hippocampal cells. KCHO‐1 can upregulate the translocation of Nrf2 and increase transcription and the expression of HO‐1 in these same cells (Lee et al, ). Another study has suggested that pretreatment of PC12 cells with the monoterpenes α‐pinene or eucalyptol prevented changes in cell morphology and viability caused by H 2 O 2 .…”
Section: Neurotoxicitymentioning
confidence: 99%
“…The exposure of astrocytes to MeHg can lead to changes in their morphology and to an increase in the rate of apoptosis. On the other hand, treatment with tea polyphenols significantly upregulated Nrf2 and its downstream genes like HO‐1 and ameliorated to a large degree the MeHg toxic effects (Lee et al, ).…”
Section: Neurotoxicitymentioning
confidence: 99%